2023
DOI: 10.1292/jvms.22-0185
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-feline infectious peritonitis virus activity of a Chinese herb extract using geneLEAD VIII, a fully automated nucleic acid extraction/quantitative PCR testing system

Abstract: The geneLEAD VIII is a fully-automated nucleic acid extraction/quantitative PCR equipment developed by Precision System Science Co. Ltd, (PSS). To take advantage of its capability, we developed a quantitative assay system to measure growth of animal viruses. The system was used to assay one of the Chinese herbal extracts whose anti-malarial activities were previously reported and demonstrated its dose-dependent anti-viral activity against feline infectious peritonitis virus (FIPV), a feline coronavirus causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Several anti-malarial drugs have been investigated for their antiviral effects. An anti-malarial Chinese herbal extract of unknown identity was found to inhibit the in vitro growth of FIP-associated FCoV [ 391 ]. Chloroquine is too toxic for cats [ 340 , 349 ], and hydroxychloroquine, although used in in vitro studies only, has been suggested as a less-toxic alternative to chloroquine [ 350 ].…”
Section: Treatment Of Fipmentioning
confidence: 99%
“…Several anti-malarial drugs have been investigated for their antiviral effects. An anti-malarial Chinese herbal extract of unknown identity was found to inhibit the in vitro growth of FIP-associated FCoV [ 391 ]. Chloroquine is too toxic for cats [ 340 , 349 ], and hydroxychloroquine, although used in in vitro studies only, has been suggested as a less-toxic alternative to chloroquine [ 350 ].…”
Section: Treatment Of Fipmentioning
confidence: 99%
“…Recent advancements in understanding the molecular biology of FIPV and therapeutic interventions have provided new insights into the management and potential eradication of the disease. A recent study has highlighted the antiviral activity of an extract from the d3 Chinese herb against FIPV, suggesting a promising avenue for natural component-based therapies (Nishijıma et al, 2023). Furthermore, flavonoids such as isoginkgetin and luteolin have been found to inhibit FIPV replication and exhibit virucidal effects, providing a foundation for the development of flavonoid-based antiviral drugs (Triratapiban et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts have been made to develop rapid, portable, and point-of-care devices that can provide nucleic acid test results. Many researchers are currently focusing on developing all-in-one nucleic acid testing devices that are faster, smaller, and more automated [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%